Phraseology as a Reflection of Linguocultural Values: A Comparative Study of Russian and French - Nurmatova , Mutabar Shuhrat qizi (The Lingua Spectrum, 2026)
This article explores phraseological units as a reflection of linguocultural values within Russian and French linguistic traditions. The study adopts a comparative approach and focuses on semantic, lexical, grammatical, and figurative features of phraseological expressions. Particular attention is given to the role of phraseology in encoding both universal human values and culture-specific meanings shaped by historical, social, and cognitive factors. The research demonstrates that Russian phraseology tends to emphasize emotional openness, spirituality, and collective experience, whereas French phraseology reflects pragmatism, rationality, and everyday material culture, especially in the domains of gastronomy and economic life. The article also examines cognitive differences manifested in phraseological semantics and highlights the importance of imagery in conveying national identity. Drawing on the works of leading scholars in phraseology and linguoculturology, the study confirms that phraseology serves as a key linguistic tool for understanding cultural worldview and intercultural communication. The findings reveal a deep interconnection between language, culture, and cognition, and underline the importance of phraseological analysis in modern linguistic research.